2009
DOI: 10.1021/cg8012238
|View full text |Cite
|
Sign up to set email alerts
|

On the Organizing Role of Water Molecules in the Assembly of Boronic Acids and 4,4′-Bipyridine: 1D, 2D and 3D Hydrogen-Bonded Architectures Containing Cyclophane-Type Motifs

Abstract: 4,4′-Bipyridine has been combined with boric acid and four different boronic acids (1,3- and 1,4-benzenediboronic acid, 3-aminophenylboronic acid, 4-acetylphenylboronic acid) to give 1:1 (with boric acid) and 1:2 adducts (with arylboronic acids), which have been characterized by X-ray diffraction analysis. The supramolecular solid-state structures are composed of hydrogen-bonded networks with (B)O−H···N, (B)O−H···O, C−H···O, C−H···N, C−H···π, π···π and C−H···B interactions. The comparative analysis of the bori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 157 publications
2
41
0
Order By: Relevance
“…In 5IQBA‐1NP similar π‐bonded dimers with antiparallel oriented isoquinolinium substituents are present, but the π ··· π contacts are now concentrated at the π–electron cloud of the atom chain C1–C4 with Cg1 ··· Cg1 (Cg1 = N1, C1–C3, C8, C9) distances (4.733 Å) that are significantly larger than in 3QBA‐1NP (Figure e). There are three B ··· N/C π contacts with the pyridinium moiety of the B‐isoquinolinium substituent, for which the central B ··· C distance of 3.161 Å is significantly shorter than the remaining contacts (3.327 and 3.632 Å) (Table ) , . Despite these differences, the supramolecular organizations of 3QBA‐1NP and 5IQBA‐1NP are quite similar within the (001) planes, as seen from a comparison of Figure d and Figure d.…”
Section: Resultsmentioning
confidence: 88%
“…In 5IQBA‐1NP similar π‐bonded dimers with antiparallel oriented isoquinolinium substituents are present, but the π ··· π contacts are now concentrated at the π–electron cloud of the atom chain C1–C4 with Cg1 ··· Cg1 (Cg1 = N1, C1–C3, C8, C9) distances (4.733 Å) that are significantly larger than in 3QBA‐1NP (Figure e). There are three B ··· N/C π contacts with the pyridinium moiety of the B‐isoquinolinium substituent, for which the central B ··· C distance of 3.161 Å is significantly shorter than the remaining contacts (3.327 and 3.632 Å) (Table ) , . Despite these differences, the supramolecular organizations of 3QBA‐1NP and 5IQBA‐1NP are quite similar within the (001) planes, as seen from a comparison of Figure d and Figure d.…”
Section: Resultsmentioning
confidence: 88%
“…Interesting, each B(OH) 2 moiety is connected to five neighboring molecules of 1 b trough hydrogen bonding interactions, two O−H⋅⋅⋅N contacts and three C−H⋅⋅⋅O contacts (Figures 5,). The hydrogen bonds and packing effects influence the less common cis behind orientation for the hydrogen atoms in the fragment B(OH) 2 , in most cases these hydrogens are oriented cis in front or in a trans disposition . The above secondary interactions supported the 2D polymeric frameworks in which the diboronic acids molecules connects the imine boronic esters chains (Figure ).…”
Section: Resultsmentioning
confidence: 89%
“…Molecules used for co-crystallization studies Although the syn,syn-conformer is found in the boronic acid-carboxylate synthon [28], the existence of this conformer with N-heterocycles is relatively rare and usually happens as a chance or with the assistance from lattice water [25,27,29]. The present study is an extension of our earlier work on the synthon preferences of various functional groups towards a 1,2,4-triazole containing drug-alprazolam (ALP) [30].…”
Section: Introductionmentioning
confidence: 93%